2005
DOI: 10.1177/1528083705053390
|View full text |Cite
|
Sign up to set email alerts
|

Some Studies on Mudar Fibers

Abstract: In this work, Mudar fibers (Calotropis procera) have been characterized for their physical, chemical, and tensile properties. Mudar fibers have good length, strength, uniformity, fineness, and excellent moisture absorption. The study highlights the difficulties in spinning 100% Mudar yarn. Subsequently, a 75/25 Mudar/cotton blend is successfully spun in a cotton spinning system and the results are analyzed. Smooth Mudar fibers develop convolutions when treated with 5% NaOH, which can render spinning possible w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 3 publications
1
29
0
Order By: Relevance
“…However, milkweed floss has been reported to have lengths up to 30 mm. 7,16 Milkweed floss also has a low percentage crystallinity compared to jute, linen and other cellulose fibers. However, the low cellulose content and percentage crystallinity should contribute to the low density of the floss fibers.…”
Section: Fiber Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, milkweed floss has been reported to have lengths up to 30 mm. 7,16 Milkweed floss also has a low percentage crystallinity compared to jute, linen and other cellulose fibers. However, the low cellulose content and percentage crystallinity should contribute to the low density of the floss fibers.…”
Section: Fiber Characterizationmentioning
confidence: 99%
“…Previous studies on characterizing various varieties of milkweed fibers have also reported similar composition of cellulose and lignin. 7,16 Milkweed floss has relatively short lengths compared to any other natural cellulose fibers in commercial use. The short length of the fibers makes it difficult for them to be processed as more common fibers and would also result in composites with inferior mechanical properties if all other fiber properties remain the same.…”
Section: Fiber Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the milkweed floss is a unique natural cellulose fiber that has a low density due to the presence of a completely hollow center. [9][10][11] No other known natural cellulose fiber has such an overall low density. 9 Consequently it will have a very low overall thermal conductivity.…”
Section: Sample Structurementioning
confidence: 99%
“…The C. procera bast fibers have been evaluated for their fiber characteristics in making cloth at a 1:1 ratio with cotton fiber (Varshney and Bhoi, 1988). The yarn has enough potential in natural fiber-reinforced composites and other industrial textile applications (Sakthivel et al 2005). The floss may also substitute cotton wool for surgical or stuffing purposes (Eisikowitch, 1986).…”
Section: Introductionmentioning
confidence: 99%